1986
DOI: 10.1016/0007-0971(86)90005-7
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis and treatment of adults with obstructive airways disease in general practice

Abstract: Two hundred and one patients diagnosed by their general practitioners as having asthma and 113 as having chronic bronchitis were compared by symptomatology and airways reversibility. Though the majority of patients given these two diagnoses could be separated by symptom complex, in about one-third such differentiation was difficult. There was no significant difference in bronchodilator reversibility between the asthmatics and chronic bronchitics. Nine out of 15 (60%) asthmatics and four out of 18 (22%) chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…Auf diesem Gebiet der Differenzierung von Asthma und COPD besteht daher unvermindert Forschungsbedarf. Das betrifft besonders die sogenannten "Mischformen", deren prozentualer Anteil an allen Patienten mit Asthma je nach Autor unterschiedlich hoch angegeben wird, aber bis zu ⅓ betragen soll [23].…”
Section: Asthma Bronchiale Und Chronische Bronchitis/copdunclassified
“…Auf diesem Gebiet der Differenzierung von Asthma und COPD besteht daher unvermindert Forschungsbedarf. Das betrifft besonders die sogenannten "Mischformen", deren prozentualer Anteil an allen Patienten mit Asthma je nach Autor unterschiedlich hoch angegeben wird, aber bis zu ⅓ betragen soll [23].…”
Section: Asthma Bronchiale Und Chronische Bronchitis/copdunclassified
“…52 In 1986, Wardman et al reported that in a general practice, a clear differentiation between asthma and COPD was difficult in 1/3rd of the patients. 53 Currently, it is unclear whether this has improved.…”
Section: Triggering Factors and Clinical Phenotypes And Presentations Of Asthmamentioning
confidence: 99%
“…This fact has been very well described in several classic publications in the British Journal of Diseases of the Chest. [28][29][30] Most patients with COPD present in the fifth or sixth decade of life although patients with alpha1-antitrypsin deficiency may present at a younger age. 4,5 Furthermore, symptoms of COPD vary among patients.…”
Section: Clinical Manifestations and Diagnosis Of Copdmentioning
confidence: 99%